Genetic relatedness of Mycobacterium tuberculosis strains obtained from Kalafong Hospital in Pretoria using Spoligotyping and MIRU-VNTR typing - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.